2014
DOI: 10.1371/journal.pone.0087339
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Host Growth after Infection with a Broad-Range Freshwater Cyanopodophage

Abstract: Freshwater cyanophages are poorly characterised in comparison to their marine counterparts, however, the level of genetic diversity that exists in freshwater cyanophage communities is likely to exceed that found in marine environments, due to the habitat heterogeneity within freshwater systems. Many cyanophages are specialists, infecting a single host species or strain; however, some are less fastidious and infect a number of different host genotypes within the same species or even hosts from different genera.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 68 publications
4
20
0
Order By: Relevance
“…Therefore, most genomic information available for phages pertains to lytic phages. Of course, phages may also change lifestyle over time, a factor which may only be determined in culture (Watkins et al 2014). Clearly, the two lifestyles may confound metagenomic survey-based examinations of total viral diversity, as sample preparation methods are largely designed to capture 'free' viruses.…”
Section: Viruses In Lake Michiganmentioning
confidence: 99%
“…Therefore, most genomic information available for phages pertains to lytic phages. Of course, phages may also change lifestyle over time, a factor which may only be determined in culture (Watkins et al 2014). Clearly, the two lifestyles may confound metagenomic survey-based examinations of total viral diversity, as sample preparation methods are largely designed to capture 'free' viruses.…”
Section: Viruses In Lake Michiganmentioning
confidence: 99%
“…Since the 1980s, research on cyanophages has focused on viruses specific to saltwater cyanobacteria [21][22][23][24][25]. In the last decade, studies have examined the diversity of freshwater cyanophages belonging to Myoviridae, Podoviridae, or Siphoviridae and their impact on their hosts, among others: Synechococcus, Microcystis, Aphanizomenon, Planktothrix, or/and Phormidium genera [11,18,19,[26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have led to the discovery of many phages, including strains Ma-LBP and ΦMHI42 from the family Podoviridae; strains Ma-LMM01, Ma-LMM02, Ma-LMM03, Ma-HPM05, and MaMV-DC from the family Myoviridae; and strain MaCV-L, which represents corticovirus-like particles [11,18,19,[26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that although host cultures were infected and eventually lysed even at the MOI as low as 10 −9 , the effect on the population growth was significantly delayed even at the high host abundance (Yoshida et al, 2006). Watkins et al, 2014 found no effect of cyanoviral infection and lysis on the growth of Planktothrix cultures at the MOI of 0.5 (Watkins et al, 2014). Thus, low initial abundances of both cyanobacteria and cyanoviruses prevent cyanovirus ability to control cyanobacteria population dynamics at the exponential phase.…”
Section: Viral Control Of Population Dynamics: Potential and Actual Ementioning
confidence: 99%
“…In addition, the initial multiplicity of infection (MOI; the number of viruses given for each individual cyanobacterial cell) can further affect the success of cyanovirus propagation. The effect of initial MOI on the ability of the cyanovirus to control cyanobacterial population growth was studied so far only in M. aeruginosa and Planktothrix (Yoshida et al, 2006;Watkins et al, 2014). It has been found that although host cultures were infected and eventually lysed even at the MOI as low as 10 −9 , the effect on the population growth was significantly delayed even at the high host abundance (Yoshida et al, 2006).…”
Section: Viral Control Of Population Dynamics: Potential and Actual Ementioning
confidence: 99%